2016
DOI: 10.1080/00268976.2016.1224393
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field phenomenology of wetting in nanogrooves

Abstract: In this special issue article we bring together our recent research on wetting in confinement, in particular planar walls, wedges, capillary grooves and slit pores, with emphasis on phase transitions and competition between wetting, filling and condensation, and highlight their similarities and disparities. The results presented are obtained with the classical density functional theory (DFT) for fluids, which is a mean-field statistical mechanical framework for including the spatial variations of the fluid den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This would allow us to evaluate the impact of the coupling between translational and rotational DoF on characteristic quantities, such as the nucleation barrier and rate. But also effects of walls [71,72] and confinement [73,[74][75][76][77], which in general should lead to definite orientation in the first particle layers near a solid substrate which in turn can induce anisotropy of both equilibrium and transport properties. Orientation coupled with layering can also cause formation of new phases in the fluid with the extreme form of the substrate-induced ordering being 'surface freezing', i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow us to evaluate the impact of the coupling between translational and rotational DoF on characteristic quantities, such as the nucleation barrier and rate. But also effects of walls [71,72] and confinement [73,[74][75][76][77], which in general should lead to definite orientation in the first particle layers near a solid substrate which in turn can induce anisotropy of both equilibrium and transport properties. Orientation coupled with layering can also cause formation of new phases in the fluid with the extreme form of the substrate-induced ordering being 'surface freezing', i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We have introduced a low- cutoff parameter in (2.6) to eliminate the non-physical divergence of at fluid–substrate contact. This is a purely mathematical device and does not affect the physics of adsorption as was shown in our earlier work (Yatsyshin & Kalliadasis 2016).…”
Section: Classical Dft Applied To Wettingmentioning
confidence: 84%
“…where ρ w is the average density of the material (w) and H 0 is a near-wall cut-off, introduced to avoid a non-physical divergence of V 0 (y) at contact with the fluid. The effect of varying the finite H 0 > 0 on planar wetting is investigated in, e.g., Appendix 1 of Reference [44], where it is shown that such low-y cut-off does not qualitatively affect the wetting phenomenology. When a macroscopically deep stripe of material type (s) of width L with the pairwise fluid-substrate potential ϕ LJ σs,εs (r) is inserted into the wall, the total potential of the decorated substrate is modified to…”
Section: Density Functional Model and Methodologymentioning
confidence: 99%
“…This allows us to perform a fully consistent mean-field analysis. Further details on the approximations involved in ( 4)-( 7), as well as full details of the numerical scheme, used to minimize the grand free energy functional and trace the full isotherms can be found elsewhere [28,44,48].…”
Section: Density Functional Model and Methodologymentioning
confidence: 99%